REPLACEMENT OF SOYBEAN WITH RAW AND PROCESSED DUCKWEED AFFECT THE PERFORMANCE AND HAEMATOLOGICAL INDICES OF NILE TILAPIA - FALAYE, A. E.; SULE, S. O.; OJO-DANIEL, H.A. (Nigerian Journal of Fisheries, 2023)
This research investigated the effects of treated duckweed meal (DWM) supplemented diets on growth, nutrients utilization and haematology of Oreochromis niloticus as soybean substitute. Nile tilapia were fed isonitrogenous diets (37% crude protein) formulated on protein for protein basis and prepared from differently treated DWM of raw (Ra), cooked (Co) and soaked in potash (So) by gradual replacement of soybean meal at Control 0; Ra5, Ra10, Ra15%; Co5, Co10, Co15% and So5, So10, So15% respectively. Juvenile O. niloticus (n=300; 12.0±0.10g; 10fish tank-1) were randomly allocated to triplicate treatments in 3×4×3 factorial experiment. The fish were fed to satiation twice daily for 84 days. Growth, nutrient utilization and haematological indices were studied. There were no significant (p>0.05) differences in performance and nutrients utilization indices of MWG, SGR and FCR amongst the treatments, except NPU (%) and survival (%) which were significantly (p<0.05) highest (85.69±1.38) in Ra10 and 95.00±3.91 in Control (0%) but lowest (75.75±1.38) in Co10 and 70.00±3.91 in Co10, respectively. PCV and haemoglobin ranged from 18.00±1.57 (Ra15) to 26.00±1.57 (Co15) and 5.95±0.50 (So10) to 7.95±0.50 (Co15), respectively, were not significantly (p>0.05) different from the control (0%). This Processing method did not improve the performance of O. niloticus fed duckweed feed efficiently above soybean, which may be due to other factors in the dietary treatments.